Factors Affecting Purchase Intention on Fashion Products - Nur Widyawati; Dian Arisanti; Hanifah Belen Fauziyyah; Aris Dwi Kurniawan; Lutfi Bayu Abadi (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: To identify and analyze the effect of perceived usefulness, perceived usefulness, benefits, trust and risks on purchase intentions for fashion products. Design / methodology / approach: The method in this study uses a quantitative approach with Structural Equation Model (SEM) berbasis Partial Least Square (PLS). Findings: The research was conducted on the millennial generation who like fashion on ZARA, UNIQLO and H&M products Research limitations / implications: Limits in the study use five independent variables and one dependent variable. The independent variables are perceived of use, perceived usefulness, benefit, trust and risk. The dependent variable is purchase intention. Practical Implications: The population in this study is millennials who buy 100 ZARA, UNIQLO and H&M products. Originality / Value: This research was conducted on ZARA, UNIQLO and H&M products.